Crime in the digital age controlling telecommunications and cyberspace illegalities - Grabosky, Peter N.; Smith, Russell G. (Transaction Publ. [u.a.], 1998)
With Crime in the Digital Age, Peter Grabosky and Russell G. Smith offer advice on the criminal opportunities that accompany the latest technological changes in telecommunications.
Keywords: Computercriminaliteit; Criminalité informatique; Delicten; Telecommunicatie; Computer crimes; Internetkriminalität; Australien